ANALISIS ALTMAN Z SCORE UNTUK MEMPREDIKSI FINANCIAL DISTRESS PADA PERUSAHAAN INDUSTRI PULP AND PAPER YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2020-2023 - Eka Ermawati (MANAJEMEN DEWANTARA, 2025)
This research discusses Altman Z score analysis to predict financial distress in pulp and paper industry companies listed on the Indonesia Stock Exchange in 2020-2023. 2020-2021 is a transition period after the Covid-19 pandemic and the paperless trend which is a threat to pulp and paper industry companies to grow and develop. The method used in this research is Quantitative Descriptive. The population in this research is all pulp and paper industry companies listed on the Indonesia Stock Exchange for the 2020-2023 period with a total of 9 companies. And the samples used were 7 company samples. sample selection using the purposive sampling method. The type of data used in this research is secondary data, namely in the form of financial reports listed on the Indonesia Stock Exchange and the data source comes from the website https://www.idx.co.id/id, the method used in this research is literature study and documentation, while the data analysis used is analyzing five financial ratios. The research results show that the majority of industrial companies are in the risk category or are likely to experience financial distress. These findings indicate the need for deeper attention to business strategy and company financial management to face economic challenges and technological developments. It is hoped that this research can contribute to company managers, investors and other interested parties in making better decisions based on the financial analysis of pulp and paper industrial companies listed on the Indonesian Stock Exchange carried out by researchers. and this research can also be a reference for further research related to Altman Z score analysis in predicting financial distress in companies in various sectors.